HUBUNGAN TINGKAT KEBAHAGIAAN TERHADAP INDEKS PRESTASI KUMULATIF (IPK) PADA MAHASISWA PRE-KLINIK FAKULTAS KEDOKTERAN DI UPN VETERAN JAKARTA SELAMA MASA PANDEMI COVID-19 - RA. Diva Berliana Denmar (2022)
Introduction: The Covid-19 pandemic that occurred in Indonesia required students, especially students, to take PJJ (Distance Lectures) lectures. The effects of the Covid-19 pandemic significantly affect the psyche and level of happiness, especially for students. Happiness is influenced by two dimensions, namely the dimensions of affection and life satisfaction. The purpose of this study was to determine the relationship between the level of happiness and the cumulative achievement index (GPA) in pre-clinical students of the Faculty of Medicine at UPN Veterans Jakarta during the COVID-19 pandemic. Methods: The research was conducted on students of FK UPN Veterans Jakarta semester 2-8 with 100 samples, the type of research descriptive-analytic method, stratified random sampling method, the calculation of the sample size was calculated by the Lemeshow formula and using the Oxford Happiness Questionnaire (OHQ) questionnaire, data in univariate and bivariate and analyzed using computerized. To determine the relationship between happiness and GPA, the fisher test was carried out. Result: Statistical analysis shows that the highest respondent's happiness level is 97% and the lowest is 3%. Most of the respondents' Grade Point Average (GPA) includes a good predicate (97%), the socioeconomic status of the respondent's family is high 70% during the covid-19 pandemic, there is no relationship which means between the level of happiness and GPA. the maximum age is 20 years (30%), 8th semester education level (30%), the respondent's family history has been exposed to Covid-19 (65%), but the respondent's history of exposure to Covid-19 is only 38%, the respondent's history of receiving booster vaccines (69%), Conclusions: There is no significant relationship between happiness based on GPA by bivariate test, but there is a tendency for a high level of happiness to get a high GPA. Sociodemographic factors that affect life satisfaction and affective factors affect the level of happiness of respondents.